Identifikasi Potensi Lokasi Markas Zona Maritim Natuna sebagai Distributor Informasi Keamanan Laut dengan Metode Centre of Gravity - Sudiro, Pratondo Ario Seno; Afpriyanto, Afpriyanto; Rizzy, Al-Fadel Arman; Bachtiar, Jefri; Jupriyanto, Jupriyanto (Universitas Mercu Buana, 2023)
Natuna Maritime Zone Region has high vulnerability to the territory violation and illegal fishing, so that it needs surveillance equipment to detect condition of maritime activities real time. Maritime Zone Quarter has function to integrate all of information from each surveillance equipment. To organize early detection system of security and safety in Indonesian sea region, Bakamla RI can be also regarded as industry player, in this case media industry. Information about security and safety at sea in real time is accepted by each surveillance equipment then gathered by the Maritime Zone Quarter and sent into the Headquarter to be analysed or as considering material to arrange law enforcement and public service at urgent situation. This research aims to determine location of Natuna Maritime Zone Quarters based on detection range of each equipment by Centre of Gravity Method, a mathematic method used to determine a location. Calculation by Microsoft Excel© obtained optimum coordinate point, (107,44;4,18). But plotting uses Google Maps© obtained position in the middle of the sea. So that three alternative locations are determined according to nearest distance from the coordinate point. There are Seluan Island (45 km), Salor Island (60 km), and Kelarik Air Mali Village in western of Great Natuna Island (62 km)